Gender inequality, water rights and policy implications: learning from the experience of experts working in water sector - Nadia Khadam; Nadia Bukhtawer; Zainab Iqbal; Hina Qayyum; Zahish Farid Khan; Munazza Razzaq; Fatima Idrees (Cogent Social Sciences, 2024)
This study explores the gender inequalities with respect to right to water by focusing on the prevalent situation of Pakistan. Discussing and debating about the water rights has become need of time as water crisis is around the globe. This depletion of water in terms of quantity as well quality has more adverse impacts on marginalised groups of which women is a focus of this research. The study in hand aims to identify gender gaps in current water laws and policies in Pakistan to highlight its impact on water governance and to make recommendations for a way forward. For this study, qualitative as well as quantitative research methodology has been employed. The deliberation upon question of relation between gender and water rights revealed that women having special needs for maintaining good hygiene, are most affected by water scarcity. Despite of this position, women have a little say at decision making tables which is one of the factors contributing towards poor water governance. In order to eradicate this issue and to bring in equity with respect to water, there needs to be an increased women representation in water sector through positive legal and policy reforms.